Karakteristik Graf Dengan Sisi Bilangan Fibonacci - Darmajid; Dwi Mifta Mahanani (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Let be a finite subset of Fibonacci numbers set. In this research, we construct a graph where the set of vertices contains integer numbers such that for every , there exist some edge in that satisfies the condition . By applying some properties of the Fibonacci numbers, we prove that if contains the first consecutive Fibonacci numbers then has the smallest order . Furthermore, we give the sufficient conditions for become simple graph and contains no cycle. Keywords: edge of graph, Fibonacci number, order of graph, simple graph, cycle.